ANALISIS BEBAN KERJA FISIK DAN TINGKAT KELELAHAN KERJA SECARA ERGONOMIS TERHADAP KARYAWAN PT. BERKAT KARUNIA PHALA DURI - Amelia Amelia; Iwan Nauli Daulay; Rio Jonnes Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
Construction worker is a high risk profession of work load. Work load that receive by the worker is beyond their ability so it can cause fatigue. Work load condition and fatigue is needed to know in order to be determined how to cope overload workload and how to prevent it. This research aims to determine physical workload level and ergonomic fatigue of employees in PT. Berkat Karunia Phala Duri. Physical workload measured by caloric needs and work fatigue is measured based on subjective fatigue measurements. The method of analysis used is descriptif analysis. Samples is taken by accidental sampling by using the slovin formula so that there are 50 respondents. From the result of research that has been done can be concluded that physical work load experienced by employees are in the middle category physical work load. While fatigue work experienced by employees are in the low category fatigue work.Keywords : physical work load, fatigue work, and ergonomic